PRE-CONCENTRATION AND DETERMINATION OF HEAVY METALS ON MODIFIED ACTIVATED CARBON IN REAL SAMPLES - F. Ahmadi; K. Niknam; A. Khanmohammadi; Z. Adibmehr (Indonesian Journal of Chemistry, 2008)
A sensitive and simple method for the simultaneous pre-concentration of nutritionally important minerals in real samples has been reported. The method is based on the formation of metal complexes by N, N'-diacetyl-4-bromo-2, 6-di (aminomethyl) phenol (DBDP) loaded on activated carbon. The metals content on the complexes are then eluted using 6mL 4M HNO3, which are detected by AAS at resonance line. In this procedure, minerals such as Ni, Cu, Co, Pb Zn and Cd can be analyzed in one run by caring out the simultaneous separation and quantification of them. At optimum condition the response are linear over concentration range of for 0.03-1.1 µg mL-1 for Ni2+ , 0.03-1.0 µg mL-1 for Cu2+, 0.02-1.0 µg mL-1 for  Pb2+ , 0.02-1.0 µg mL-1 for  Co2+,0.02-1.1 µg mL-1 Zn2+ and 0.05-1.3 µg mL-1for Cd2+. The detection limits of each element are expressed as the amount of analytes in µg mL-1 giving a signal to noise ratio of 3 are equal to 2.5, 2.4, 1.6, 2.4, 1.9 and 2.1 for Ni2+ , Cu2+, Pb2+ , Co2+,Zn2+ and Cd2+. The ability of method for repeatable recovery of trace ion are 99.9, 98.7, 99.2 , 98.7, 98.5and 95.6 with R.S.D of 1.3, 1.4, 1.2, 1.4, 1.7 and 1.4 for Ni2+ , Cu2+, Pb2+ , Co2+,Zn2+ and Cd2+. The method has been successfully applied for these metals content evaluation in some real samples including natural water and vegetable.